Global range extension of bioclimatic zone of Bruguiera hainesii C.G.Rogers 1919 (Rhizophoraceae) - Mai-Phuong Pham; Thi Thu Trang Hoang; Van Dien Pham; Thanh Trang Pham; Dinh Duy Vu (One Ecosystem)
Bruguiera hainesii is a rare mangrove species with limited populations worldwide, but there is lack of detailed knowledge about its population size and distribution in Vietnam. Its regeneration capacity is notably low, raising concerns about its long-term survival. This study aims to model the bioclimatic niche of B. hainesii to identify potential ecological regions in Vietnam suitable for its conservation and survival under current and future climate scenarios. Occurrence data were collected from the global GBIF database and recent field surveys in Vietnam conducted during 2023–2024. The Maxent model was used to predict bioclimatic suitability, with projections extended to future climate scenarios using ACCESS-CM2 under SSP2-4.5 (medium-emission scenario) for 2080–2100. The study identified Vietnam as a highly suitable region for B. hainesii despite its small population size. Projections indicate a potential expansion of ideal habitats under future climate conditions, highlighting the species' adaptability. The findings provide valuable insights into the conservation of B. hainesii, emphasising the importance of preserving existing populations and managing suitable habitats to ensure the species' long-term survival and regeneration. This research also underscores the role of bioclimatic niche modelling in guiding conservation strategies for endangered mangroves.